Organoleptic Test of Choco Cookies Made from Breadfruit Flour - Putra, Santya Wijaya; Atmaja, I Made Purwa Dana (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This study aims to present a review of the organoleptic characteristics of choco cookies and the development of product variations enriched with chocolate. Due to the lack of breadfruit processing, alternative processing is needed to utilize breadfruit optimally. The method used in this study is descriptive qualitative which aims to determine and describe the organoleptic quality of choco cookies using breadfruit flour which is reviewed from the taste, aroma, texture and color. The results of this breadfruit flour choco cookies study in terms of taste obtained an index value of 86%, in terms of aroma obtained an index value of 87%, in terms of texture obtained an index value of 84%, in terms of color obtained 81%, with an average total of 84.5%. So the results of the experiment on choco cookies made from breadfruit flour were successful.